Increased mean platelet volume is associated with non-responsiveness to clopidogrel - Asher, Elad; Fefer, Paul; Shechter, Michael; Beigel, Roy; Varon, David; Shenkman, Boris; Savion, Naphtali; Hod, Hanoch; Matetzky, Shlomi (Thrombosis and Haemostasis, 2014)
Prior studies have demonstrated significant individual variability of platelet response to clopidogrel, which affects clinical outcome. In patients with stable coronary artery disease (CAD) smoking, diabetes mellitus, elevated body mass index and renal insufficiency, significantly impact response to clopidogrel. The determinants of platelet response to clopidogrel in patients with acute coronary syndrome are unknown. Adenosine diphosphate (ADP)-induced platelet aggregation (PA), hs C-reactive protein, platelet count and mean platelet volume (MPV) were determined 72 hours post clopidogrel loading in 276 consecutive acute myocardial infarction (AMI) patients. Patients with ADP-platelet aggregation ≥ 70% were considered to be clopidogrel non-responders. Eighty-four patients (30%) were clopidogrel non-responders and 192 (70%) were responders (ADP-induced PA: 81 ± 17% vs 49 ± 17%, respectively, p<0.001). Both study groups were comparable with respect to age, gender, prior cardiovascular history, prior aspirin use and risk factors for CAD, including smoking (42% for both groups) and diabetes mellitus (26% vs 22%, respectively, p=0.4). Responders and non-responders had similar angiographic characteristics, indices of infarct size, and similar hs-CRP (29 ± 34 vs 28 ± 34 mg/l, p=0.7) and creatinine (1.08 ± 0.4 mg% vs 1.07 ± 0.4, p=0.9) levels. On the contrary non-responders had significantly larger mean MPV (9 ± 1.2 fl vs 8 ± 1 fl, respectively, p=0.0018), and when patients were stratified into quartiles based on MPV, ADP-induced PA increased gradually and significantly across the quartiles of MPV (p<0.001). In conclusion, increased MPV associated with platelet activation, predicts non-responsiveness to clopidogrel among patients with acute coronary syndrome.
Keywords: Acute coronary syndrome; platelet activation; response to clopidogrel; mean platelet volume